2013
DOI: 10.1590/s0004-27492013000300005
|View full text |Cite
|
Sign up to set email alerts
|

Corneal thickness changes during corneal collagen cross-linking with UV-A irradiation and hypo-osmolar riboflavin in thin corneas

Abstract: Purpose: To evaluate the thinnest corneal thickness changes during and after corneal collagen cross-linking treatment with ultraviolet-A irradiation, using hypo-osmolar riboflavin solution in thin corneas. Methods: Eighteen eyes of 18 patients were included in this study. After epithelium removal, iso-osmolar 0.1% riboflavin solution was instilled to the cornea every 3 minutes for 30 minutes. Hypo-osmolar 0.1% riboflavin solution was then applied every 20 seconds for 5 minutes or until the thinnest corneal thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…No significant change was noticed in the pachymetry readings after UV-A radiation compared with the preoperative pachymetry reading. 8,[10][11][12][13] A modification to the technique of CXL was introduced, so that corneas thinner than 400 mm after abrasion of the epithelium become eligible for treatment. 7 HPMC is nonirritant to ocular tissue and can be used for prolonged periods without any damage to the eye.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No significant change was noticed in the pachymetry readings after UV-A radiation compared with the preoperative pachymetry reading. 8,[10][11][12][13] A modification to the technique of CXL was introduced, so that corneas thinner than 400 mm after abrasion of the epithelium become eligible for treatment. 7 HPMC is nonirritant to ocular tissue and can be used for prolonged periods without any damage to the eye.…”
Section: Discussionmentioning
confidence: 99%
“…7 HPMC is nonirritant to ocular tissue and can be used for prolonged periods without any damage to the eye. 12 Keeping these facts in perspective, we modified our study and used isotonic riboflavin with HPMC during the saturation phase and the accelerated protocol thereby reducing the duration of UV-A irradiation to 10 minutes instead of 30 minutes. Also, compared with the breakup time of the dextran-riboflavin film, which is 22 minutes, HPMC-riboflavin is approximately 32 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group (25) recently described transient corneal thinning after corneal CXL with UVA irradiation and a hypo-osmolar riboflavin solution in thin corneas (<400 µm) for progressive keratoconus. In our analysis of changes in corneal thickness over time, pachymetric values decreased until 1 month after surgery and appeared to increase thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…According to "equal-dose" principle 10mW/cm and reducing the exposure time to 9 minutes produces a similar increase in corneal stiffness to that gained using the standard procedure 66 . Several recent in vivo studies using different protocols showed the procedure to be safe and effective in stopping ectasia progression [69][70][71][72] . Kanellopoulos AJ 57 reported efficacy of CXL in early keratoconus with riboflavin delivered in a femtosecond laser-created pocket, thus avoiding the need to remove the epithelium or use other drugs.…”
Section: Accelerated Corneal Crosslinking (A-cxl)mentioning
confidence: 99%